2021
DOI: 10.1186/s12931-020-01598-4
|View full text |Cite
|
Sign up to set email alerts
|

Resistin-like molecule β acts as a mitogenic factor in hypoxic pulmonary hypertension via the Ca2+-dependent PI3K/Akt/mTOR and PKC/MAPK signaling pathways

Abstract: Background Pulmonary arterial smooth muscle cell (PASMC) proliferation plays a crucial role in hypoxia-induced pulmonary hypertension (HPH). Previous studies have found that resistin-like molecule β (RELM-β) is upregulated de novo in response to hypoxia in cultured human PASMCs (hPASMCs). RELM-β has been reported to promote hPASMC proliferation and is involved in pulmonary vascular remodeling in patients with PAH. However, the expression pattern, effects, and mechanisms of action of RELM-β in H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…Emerging evidence has demonstrated that AKT signalling participates in the modulation of the phenotypic switch, proliferation, and migration of PASMCs in PAH. 25 , 26 , 27 In addition, Pitre et al showed that SYN positively promotes glioblastoma cell proliferation by promoting AKT activation. 17 As shown in Figure 5 A , SYN suppression inhibited AKT activation in hPASMCs, whereas SYN overexpression resulted in the opposite result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has demonstrated that AKT signalling participates in the modulation of the phenotypic switch, proliferation, and migration of PASMCs in PAH. 25 , 26 , 27 In addition, Pitre et al showed that SYN positively promotes glioblastoma cell proliferation by promoting AKT activation. 17 As shown in Figure 5 A , SYN suppression inhibited AKT activation in hPASMCs, whereas SYN overexpression resulted in the opposite result.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that the activation of AKT promotes phenotypic switch, proliferation, and migration of PASMCs, thus intensifying pulmonary vascular remodelling in PAH. 25 , 26 , 27 In addition, it has been demonstrated that SYN enhances the proliferation of glioblastoma cells via activation of the AKT signalling pathway. 17 Here, we provided direct evidence that SYN overexpression promoted hPASMCs dysfunction, and these effects were reversed by an AKT inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“… 27 After treating pulmonary arterial smooth muscle cells with exogenous recombinant RELMβ protein, the levels of phosphorylated MAPK and PKC increased, which was accompanied by a significant increase in cell viability. 14 It has been shown that erythromycin inhibits p38 MAPK phosphorylation in patients with chronic obstructive pulmonary disease, thereby improving sensitivity to glucocorticoids and reducing the level of inflammation in patients with chronic obstructive pulmonary disease. 28 The studies described above suggest that RELMβ, together with the MAPK signaling pathway, plays a vital role in regulating airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 13 In addition, RELMβ overexpression in mice causes hemodynamic changes, including increased mean proper ventricular systolic pressure, right heart hypertrophy, and small pulmonary artery constriction. 14 The current understanding of the mechanism by which RELMβ contributes to pulmonary inflammation is mainly derived from studies of RELMα, which is highly homologous to RELMβ. 15 In a study of rat alveolar epithelial cell inflammation in response to tobacco smoke extract, IL-8 secretion into the supernatant was correlated with RELMα expression in a time-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…These serine-threonine protein kinases play critical roles in the regulation of many cellular processes including cell cycle, proliferation, and apoptosis [ 21 , 22 ]. Previous studies have shown that hypoxia promoted cell proliferation and inhibited apoptosis of PASMCs and sequentially induced pulmonary vascular remodeling via phosphorylated activation of ERK, JNK, and P38 signaling pathways [ 23 25 ]. Several studies have demonstrated that Notch4 was involved in the regulation of survival and migration of tumor and endothelial cells via MAPK signaling pathways [ 26 29 ].…”
Section: Introductionmentioning
confidence: 99%